Determination and Study of Main Biological Features of Bacteriophages Active Against Bacteria Pseudomonas fluorescens and Pseudomonas aeruginosa - Mohmed Al-shahrani,; Abdulkhaleg Elhedmi,; Abdulkhaleg Elhedmi,; Hossam Elkaib,; Samira Jrad,; Shaymaa Alnaqib, (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. One of the significant areas of modern microbiology and biotechnology is the study of bacteriophages. This is due to the growing interest in terms of their practical application in various branches of medicine, agriculture, and the food industry. The purpose of our work was to isolate bacteriophages active against bacteria of the genus Pseudomonas and to study their biological properties. Methods. Bacteriophages isolated from spoiled poultry, beef and carp samples were the subjects of the study. 20 g of the weighed sample were inoculated with 20μl of Pseudomonas spp. diluted 24 hrs culture and incubated at 30°C for 2 days, the cultures were infected with phages at a dose of 0.1 ml and continued cultivation for another 4– 5 h until onset of culture lysis. Results. In the studies, 8 bacteriophages were isolated, of which 4 are active against P. fluorescens bacteria (BV-4, BV-5, BV-55, BV-71) and 4 were active against P. aeruginosa bacteria (BV-12, BV-23, BV-25, BV-57). Negative colonies of bacteriophages specific to P. aeruginosa were characterized by the following parameters: diameter 3.0–4.5 mm, completely transparent, without a zone of secondary lysis; and phages specific to P. fluorescens had a diameter of 2.0–4.0 mm, were completely transparent, without a zone of secondary lysis. Conclusions. Protecting protein-containing foods that have not undergone heat treatment from microbial contamination by using strains of bacteriophages BV-25 and BV-55, Showed efficacy against bacteria of the genus Pseudomonas.